Simultaneous Determination of 5 Components in the Leaves of Dimocarpus longan by Quantitative Analysis of Multicomponents by Single Marker (QAMS) Based on UPLC and HPLC - Jiani Mai; Jie Liang; XianFu Liu; LiuPing Tan; Hui Xu; YaoHua Li; YuShan Zhou; ChuanChuan Yang; ChenXi Xin (Journal of Analytical Methods in Chemistry)
The pharmacodynamic effect of longan leaves was attributed to various components, especially the flavonoids. In this paper, a new strategy of quantitative analysis of multicomponents by a single marker (QAMS) method was first established to synchronously determine 5 components (ethyl gallate (C1), astragalin (C2), quercetin (C3), luteolin (C4), and kaempferol (C5)) in Dimocarpus longan by ultra-performance liquid chromatography (UPLC) and high-performance liquid chromatography (HPLC). Quercetin (C3) was chosen as the internal reference. Relative correction factors (RCFs, ƒs/i) of the other 4 components were calculated by two correction methods (multipoint correction and slope correction) to effectuate QAMS. At the same time, the difference between the results measured by the QAMS and external standard methods was compared to verify the accuracy of QAMS. Within the linear range, the results showed that all ƒs/i values were obtained with good durability under diverse chromatographic conditions (RSD < 2.28%). The quantitative results of 5 components in the leaves of Dimocarpus longan collected from 10 producing areas by different chromatographic systems and quantitative methods were significantly correlated (Pearson’s r > 97.0%). The applicability and feasibility of the QAMS method established in this study were evaluated to be favorable for quality control of the leaves of Dimocarpus longan. As a new model of quality control, it can provide one more choice of multicomponent quality-control method in the absence of standard substances or instruments.